Xiao-Yin-Fang Therapy Alleviates Psoriasis-like Skin Inflammation Through Suppressing γδT17 Cell Polarization - Zhang, Xilin; Li, Xiaorui; Chen, Youdong; Li, Bingjie; Guo, Chunyuan; Xu, Peng; Yu, Zengyang; Ding, Yangfeng; Shi, Yuling; Gu, Jun (Frontiers in Pharmacology, 2021)
Psoriasis is an immune-mediated chronic inflammatory skin disease primarily mediated by the activation of interleukin (IL)-17-producing T cells. Traditional Chinese Medicine (TCM) represents one of the most effective complementary and alternative medicine (CAM) agents for psoriasis, which provides treasured sources for the development of anti-psoriasis medications. Xiao-Yin-Fang (XYF) is an empirically-developed TCM formula that has been used to treat psoriasis patients in Shanghai Changhai Hospital for over three decades. Imiquimod (IMQ)-induced psoriasis-like dermatitis mouse model was utilized to investigate the therapeutic effects of XYF by the assessment of disease severity and skin thickness. Flow cytometric assay was performed to explore the influence of XYF on skin-related immunocytes, primarily T cells. And, RNA sequencing analysis was employed to determine the alternation in gene expression upon XYF therapy. We discovered that XYF alleviated psoriasis-like skin inflammation mainly through suppressing dermal and draining lymph-node IL-17-producing γδT (γδT17) cell polarization. Moreover, XYF therapy ameliorated the relapse of psoriasis-like dermatitis and prohibited dermal γδT cell reactivation. Transcriptional analysis suggested that XYF might regulate various inflammatory signaling pathways and metabolic processes. In conclusion, our results clarified the therapeutic efficacy and inner mechanism of XYF therapy in psoriasis, which might promote its clinical application in psoriasis patients and facilitate the development of novel anti-psoriasis drugs based on the bioactive components of XYF.